FAKTOR – FAKTOR YANG TERKAIT DENGAN EKSPOR CRUDE PALM OIL (CPO) - Fauzul Azhimah; Chaula Lutfia Saragih (Universitas Quality, 2019)
This study aims to analyze the balance of long-term and error term, CPO export prices, world soybean oil prices, domestic CPO production, inflation, exchange rate, export tax applicable to the export volume of CPO. The analytical method used Engle Granger cointegration analysis,Error Correction Model (ECM) and completed with E-Views. The research data is secondary weeklydata from year 2006 - 2015. The data is analyzed by Engel Granger cointegration and Error Correction Modelmethod. The result of the analysis shows that there is a positive correlation between CPO export price, soybean oil and domestic CPO to export of CPO. While the inflation, exchange rate, and export tax variables show a negative correlation to CPO exports. In estimation of error-term, there is a positive correlation to CPO export price variables, soybean oil price and CPO domestic production. While the variables of inflation, exchange rate and export tax show negative correlation to CPO exports.